Introduction to the GaLA Conf 2019 Special Issue - Manuel Gentile; Mario Allegra; Heinrich Heinrich Söbke (International Journal of Serious Games, 2019)
This issue contains seven selected articles, which gives an overview of the rich field of serious games. So among the topics covered in this issue there are: